Comparison of Health Issues Faced by Business Leaders in Japan and Indonesia - Hokama, Naoki (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Modern business leaders act as compasses for their companies, shouldering the responsibility to steer them. They are exposed daily to a multitude of pressures, including fierce market competition, constantly shifting economic landscapes, and increasing social responsibility. In such a demanding environment, the mental and physical health of leaders becomes an exceptionally critical resource that determines business sustainability. A leader's state of health directly affects their ability to make sound decisions, their capacity for leadership that boosts employee morale, and the overall productivity of the organization. Consequently, managing a leader's health is increasingly recognized not merely as a personal matter but also as a strategic imperative essential for corporate growth and stability.